Case Report: A Novel KMT2E Splice Site Variant as a Cause of O'Donnell-Luria-Rodan Syndrome in a Male Patient - Cao, Zixuan; Wang, Chunli; Chen, Jing; Guo, Hu; Wu, Chunfeng; Zhang, Gang; Ding, Le (Frontiers in Pediatrics, 2022)
Background: O'Donnell-Luria-Rodan (ODLURO) syndrome is an autosomal dominant systemic disorder characterised by global developmental delay caused by mutations in the KMT2E gene. The aim of this study was to investigate the role of KMT2E mutations as a cause of ODLURO syndrome in a Chinese boy. Methods: We reported the clinical course of a Chinese boy who was diagnosed with ODLURO syndrome by the whole exome sequencing. We extracted genomic DNA of the proband and parents,gene variations were screened using whole-exome sequencing,followed by validation using direct Sanger sequencing. The effect of mRNA splicing variants were analyzed through a minigene splice assay and in vitro reverse transcription PCR (RT-PCR). Results: The proband presented with recurrent seizures and developmental delay. Using genetic analysis, we identified that the proband carried a de novo heterozygous splicing variant (c.1248+1G>T) in the KMT2E gene. In vivo transcript analysis showed that the proband did not carry any KMT2E mRNA transcript, while a specific exon11-exon13 (440bp) transcript was detected in the unaffected parents. The in vitro minigene splice assay conducted in HEK293 cells confirmed that the c.1248+1G>T variant resulted in exon 12 skipping, which in turn caused an alteration in KMT2E mRNA splicing. The mutant transcript created a premature stop codon at the 378 amino acid position that could have been caused nonsense-mediated mRNA decay (NMD). Conclusion: We verified the pathogenic effect of the KMT2E c.1248+1G>T splicing variant, which disturbed normal mRNA splicing and caused mRNA decay. Our findings suggest that splice variants play an important role in the molecular basis of ODLURO, and that careful molecular profiling of these patients could play an essential role in tailoring of personalized treatment options soon.